Strategi Inovasi Proses Bisnis dalam Pemasaran: Optimalisasi Layanan Pelanggan melalui Teknologi Baru untuk Peningkatan Kepuasan dan Loyalitas Pelanggan - Mahfud Nurnajamuddin; Serlin Serang; Chici Adriani; Andi Alif Aqris M (Journal of Innovative and Creativity, 2026)
Increasingly fierce marketplace competition has made customer service quality the key differentiating factor in retaining customers. Amid rising customer expectations for fast, consistent, and accessible services, business process innovation in marketing and the utilisation of new technology need to be urgently reviewed, as both have the potential to determine customer satisfaction and loyalty. This study aims to analyse the influence of Business Process Innovation in Marketing and New Technology on Customer Satisfaction and Customer Loyalty through Customer Service Optimisation in the context of the marketplace in Makassar City. This study uses a quantitative approach with an explanatory research type. The research population consists of marketplace users in Makassar City who have made transactions and used customer services. The sampling technique used purposive sampling with a sample size of 320 respondents. Data collection was conducted through questionnaires and analysed using the PLS SEM method with the assistance of SmartPLS to test the measurement model and structural model. The results of the study indicate that business process innovation in marketing and new technology play a role in improving customer service optimisation, and customer service optimisation encourages customer satisfaction and loyalty. The findings also confirm that customer service optimisation is an important mechanism that bridges the influence of process and technological innovation on satisfaction and loyalty. The implications of this study emphasise the need for marketplaces to prioritise service process innovations that reduce customer friction and integrate new technologies appropriately in order to produce a more effective and sustainable service experience.